I Robot: U Tax? Considering the Tax Policy Implications of Automation - Mann, Roberta (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
In a 2017 interview, Microsoft founder Bill Gates recommended taxing robots to slow the pace of automation. Funds raised could be used to retrain and financially support displaced workers. Up to 47 per cent of US jobs are at risk by advancements in artificial intelligence. Low-wage workers currently hold a majority of those at-risk jobs. Increased automation is likely to exacerbate income inequality.While employment changes due to automation are not new, advances in artificial intelligence threaten to eliminate many more jobs than were eliminated historically through automation. Accelerated automation presents two problems: a revenue problem and a human problem. The revenue problem exists because the tax system is designed to tax labour more heavily than capital, as labour is less likely to be able to avoid taxation. Capital investment, on the other hand, is taxed more lightly because capital is mobile and can escape taxation. When capital becomes labour, as in automation, the bottom falls out of the system. The human problem is first that most people need income from working to survive. Some scholars have advocated for a governmentally provided universal basic income (UBI). Taxing robots could in theory provide revenue for a UBI, although any source of revenue would work just as well. While a UBI would solve the survival problem, humans need more than basic survival. In his classic work, psychologist Abraham Maslow listed survival as the foundation of his hierarchy of needs. Work satisfies the higher order needs of social identity and self-esteem.The Tax Cuts and Jobs Act (TCJA), enacted in December 2017, significantly cut the US corporate tax rate, from 35 per cent to 21 per cent. In addition, TCJA increased tax benefits for purchasing equipment (which would include automation) by significantly enhancing bonus depreciation. The new tax legislation continued and deepened the existing tax bias towards automation. This article explores policy options for solving the revenue problem and the "jobs" problem, including a discussion and critique of UBI proposals and recommendations for other policy options, such as an enhanced earned income tax credit, incentives for employers, and reviving an idea from the Great Depression, the Civilian Conservation Corps.